1997
DOI: 10.1021/bi962284z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Human α-1,3-Fucosyltransferase V:  Glycosidic Cleavage Occurs Prior to Nucleophilic Attack

Abstract: R-1,3-Fucosyltransferase V (FucT V) catalyzes the transfer of l-fucose from the donor sugar guanosine 5′-diphospho--l-fucose (GDP-Fuc) to an acceptor sugar. A secondary isotope effect on the fucosyltransfer reaction with guanosine 5′-diphospho-[1-2 H]--l-fucose (GDP-[1-2 H]-Fuc) as the substrate was observed and determined to be D V ) 1.32 ( 0.13 and D V/K ) 1.27 ( 0.07. Competitive inhibition of FucT V by guanosine 5′-diphospho-2-deoxy-2-fluoro--l-fucose (GDP-2F-Fuc) was observed with an inhibition constant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 41 publications
(64 reference statements)
7
91
0
3
Order By: Relevance
“…The involvement of an oxocarbenium ion transition state in the chemical mechanisms of glycosyltransferases and glycosidases is well supported. Significant normal ␣-deuterium secondary isotope effects have been reported for inverting and retaining glycosyltransferases (45)(46)(47) and glycosidases (48,49) consistent with C1-O bond cleavage occurring prior to attack by the acceptor sugar or water. For inverting glycosidases and glycosyltransferases, the proposed single displacement mechanism is well established (50).…”
Section: Resultsmentioning
confidence: 92%
“…The involvement of an oxocarbenium ion transition state in the chemical mechanisms of glycosyltransferases and glycosidases is well supported. Significant normal ␣-deuterium secondary isotope effects have been reported for inverting and retaining glycosyltransferases (45)(46)(47) and glycosidases (48,49) consistent with C1-O bond cleavage occurring prior to attack by the acceptor sugar or water. For inverting glycosidases and glycosyltransferases, the proposed single displacement mechanism is well established (50).…”
Section: Resultsmentioning
confidence: 92%
“…Mammalian ␣1,3/4 FucTs, especially human FucTs, have been extensively characterized with regard to the key polar group of the acceptors (25, 29), the domain or amino acid residues responsible for donor binding (30 -33) and acceptor recognition (15-18, 29 -32), and kinetic mechanisms (33)(34)(35). The study of bacterial ␣1,3/4 FucTs, in contrast, is not as far advanced.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these His, Glu, and Asp residues can be considered as candidates for the formation of hydrogen bonds with the acceptor oligosaccharide. Based on recent studies, it seems reasonable to suggest that the active-site base in the protein may be a carboxylate anion (33,34). In another study, Britten and Bird (35) investigated the amino acids essential for the activity of Fuc-TVI through chemical modification, and they concluded that the substratebinding site of the enzyme possesses His residue(s) that are essential for enzyme activity.…”
Section: Discussionmentioning
confidence: 99%